Reimagining libraries for a post-pandemic world : Proceedings of the International 8th Conference on Libraries, Information and Society, ICoLIS 2021, Kuala Lumpur, Malaysia, 18-19 August 2021 - Mohd. Khalid, Yanti Idaya Aspura (Department of Library and Information Science, Faculty of Computer Science and Information Technology, University of Malaya and University of Malaya Library, 2021)
Organised by: Department of Library and Information Science, Faculty of Computer Science and Information Technology, University of Malaya and University of Malaya Library.